2012
DOI: 10.1128/jvi.06295-11
|View full text |Cite
|
Sign up to set email alerts
|

The Insulator Protein CTCF Binding Sites in the orf73 /LANA Promoter Region of Herpesvirus Saimiri Are Involved in Conferring Episomal Stability in Latently Infected Human T Cells

Abstract: Herpesviruses establish latency in suitable cells of the host organism after a primary lytic infection. Subgroup C strains of herpesvirus saimiri (HVS), a primate gamma-2 herpesvirus, are able to transform human and other primate T lymphocytes to stable growth in vitro. The viral genomes persist as nonintegrated, circular, and histone-associated episomes in the nuclei of those latently infected T cells. Epigenetic modifications of episomes are essential to restrict the transcription during latency to selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Additionally, the IR bears a predicted, consensus binding site for the DNA-binding protein CTCF (CCCTC-binding factor), a well-known, ubiquitously expressed nuclear protein, highly conserved from Drosophila to mouse and man. CTCF is prominently involved in the three-dimensional organization of chromatin and a key player in transcriptional regulation in vertebrates37, while it appears to possess strong insulating activity in vitro 38. Importantly, it has been found to confer episomal stability to herpesvirus genomes in latently infected human T cells38.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the IR bears a predicted, consensus binding site for the DNA-binding protein CTCF (CCCTC-binding factor), a well-known, ubiquitously expressed nuclear protein, highly conserved from Drosophila to mouse and man. CTCF is prominently involved in the three-dimensional organization of chromatin and a key player in transcriptional regulation in vertebrates37, while it appears to possess strong insulating activity in vitro 38. Importantly, it has been found to confer episomal stability to herpesvirus genomes in latently infected human T cells38.…”
Section: Discussionmentioning
confidence: 99%
“…Primary rhesus fibroblasts (kindly provided by A. Kaur, Harvard Medical School, Southborough, MA), OMK cells, and Vero cells were cultivated in Dulbecco's minimal essential medium (Gibco/BRL, Eggenstein, Germany) supplemented with 10% fetal calf serum and gentamicin. The HVS strain employed in this study was obtained by reconstitution of infectious viruses using Bac43MOD containing the genomic sequence of HVS strain C488 (10) and a cytomegalovirus (CMV) immediate-early promoter-driven enhanced green fluorescent protein (EGFP) expression cassette inserted in the SwaI site at position 5656, analogous to earlier descriptions (42,47). Stocks of wild-type (wt) and recombinant viruses were prepared, and the amount of viral genomes in the supernatant of infected OMK cells was quantified by quantitative PCR of the MCP locus with primers MCP_for (5=-CCATTTGCCTGTGTTGAGAGTTAA-3=) and MCP_rev (5=-CTCATTACCAGACCCATGTTATGAA-3) and probe MCP_probe (5=/56-FAM/CTCCGAGAG/ZEN/AGCCTATCTGAGATG CCC/3lABkFQ/-3=, where FAM is 6-carboxyfluorescein, ZEN is internal ZEN Quencher, and 3IABKFQ is 3= Ioua Black FQ Quencher) (Integrated DNA Technologies, Coralville, IA).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Herpesviruses are characterized by their ability to establish lifelong latency in the host. Only limited numbers of viral genes are expressed during latent infection, while multiple copies of the viral genome persist as circular episomes within the nuclei of host cells (Zhou & Gao 2011;Zielke et al 2012). Our PCR results indicated that the left and right TRs of the CyHV-3 genome were fused in a head-to-tail manner followed by sequence rearrangements by temperature upshift from 25°C to 35°C.…”
Section: Influence Of Temperature Shift On Cyhv-3 Replicationmentioning
confidence: 79%